In Utero Exposure to Maternal Overweight or Obesity is Associated with Altered Offspring Brain Function in Middle Childhood. Issue 9 (8th August 2020) - Shapiro, Allison L. B.; Moore, Brianna F.; Sutton, Brianne; Wilkening, Greta; Stence, Nicholas; Dabelea, Dana; Tregellas, Jason R.
Abstract : Objective: The impact of in utero exposure to maternal overweight and obesity on offspring metabolic health is well documented. Neurodevelopmental outcomes among these children are, however, less well studied. To address this gap, the current study investigated brain function among 4‐ to 6‐year‐old children exposed to maternal overweight or obesity during gestation compared with that of children born to mothers with healthy BMI in pregnancy. Methods: Resting‐state functional magnetic resonance imaging was used to study neuronal activity and connectivity during a passive viewing task (movie) among 101 typically developing children enrolled in the Healthy Start study, a longitudinal prebirth cohort in Colorado. Results: Forty‐nine children (48%) were exposed to maternal overweight or obesity in utero (mean age = 5 years, SD = 0.9). Children born to mothers with overweight or obesity demonstrated hyperactivity in the left posterior cingulate cortex and hypoactivity in the dorsal anterior cingulate and the supplementary motor area ( P  < 0.05 for all). Children born to mothers with overweight or obesity also showed ubiquitously weaker brain connectivity ( P  < 0.05 for all). Conclusions: These novel results suggest altered brain function among children exposed to maternal overweight and obesity in utero .